2017
DOI: 10.1182/blood.v130.suppl_1.82.82
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic-Specific CSNK2B Loss in Mice Causes Impaired Erythropoiesis

Abstract: CK2 (Csnk2, casein kinase 2) is a Ser-Thr kinase composed by two catalytic (α) and two regulatory (β) subunits and involved in the regulation of various signaling cascades, which are critical for stem cell biology and hematopoietic development. However, a direct role for CK2 during blood cell differentiation is still undefined. Here, we examined the function of CK2 in erythropoiesis by using a hematopoietic-specific conditional knockout mouse model of the β regulatory subunit (Vav1-CRE x Csnk2β f/f mice). Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, the role of CSNK2B in regulating erythropoietic response was functionally evaluated in both CMS and non-CMS cells ( Figure 5 ) and in vivo in zebrafish ( Figure 6, A–C ). Interestingly, a recent study, published in an abstract form, also showed that Csnk2b is a critical regulator of erythropoiesis in mice ( 28 ). In this mouse model with a hematopoietic-specific conditional KO of Csnk2b (i.e., Vav1-CRE × Csnk2β fl/fl mice), Piazza’s and colleagues found that Csnk2b deficiency was lethal in utero and that fetuses displayed a severe anemic phenotype, suggesting that loss of Csnk2b altered erythroid development and led to defects of red cell viability ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the role of CSNK2B in regulating erythropoietic response was functionally evaluated in both CMS and non-CMS cells ( Figure 5 ) and in vivo in zebrafish ( Figure 6, A–C ). Interestingly, a recent study, published in an abstract form, also showed that Csnk2b is a critical regulator of erythropoiesis in mice ( 28 ). In this mouse model with a hematopoietic-specific conditional KO of Csnk2b (i.e., Vav1-CRE × Csnk2β fl/fl mice), Piazza’s and colleagues found that Csnk2b deficiency was lethal in utero and that fetuses displayed a severe anemic phenotype, suggesting that loss of Csnk2b altered erythroid development and led to defects of red cell viability ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study, published in an abstract form, also showed that Csnk2b is a critical regulator of erythropoiesis in mice ( 28 ). In this mouse model with a hematopoietic-specific conditional KO of Csnk2b (i.e., Vav1-CRE × Csnk2β fl/fl mice), Piazza’s and colleagues found that Csnk2b deficiency was lethal in utero and that fetuses displayed a severe anemic phenotype, suggesting that loss of Csnk2b altered erythroid development and led to defects of red cell viability ( 28 ). Our results in this work (humans and zebrafish) as well as Piazza’s work in mice hence demonstrate that CSNK2B is evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%